2015
DOI: 10.1016/j.ddtec.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics in drug development

Abstract: Numerous human pathologies, including common conditions such as obesity, diabetes, cardiovascular disease, cancer, inflammatory disease and neurodegeneration, involve changes in lipid metabolism. Likewise, a growing number of drugs are being developed that directly or indirectly affect lipid metabolic pathways. Instead of classical and cumbrous radiochemical analyses, lipid profiling by mass spectrometry (MS)-based lipidomics holds great potential as companion diagnostic in several steps along the drug develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Lipidomics is an exciting new area 26 . It has been widely applied in several disciplines, including neuroblastoma 27 , mammalian cancer 28 , prostate cancer 29 , tetrahydrocannabinol addiction 30 , Alzheimer’s Disease 31 and drug development 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics is an exciting new area 26 . It has been widely applied in several disciplines, including neuroblastoma 27 , mammalian cancer 28 , prostate cancer 29 , tetrahydrocannabinol addiction 30 , Alzheimer’s Disease 31 and drug development 32 .…”
Section: Discussionmentioning
confidence: 99%
“…166 Replacement of the central ring by pyridine resulted in similar effects on potency and lipophilicity as for the terminal position. 166 Appending polar substituents resulted in the significantly less lipophilic and more polar compound TUG-488 (12). 167 Investigations of their ability to permeate mucus producing membranes indicated better penetration for 10 and 12 than for 11.…”
Section: Synthetic Ligands For Ffa1mentioning
confidence: 97%
“…19, 20 Indeed, recent lipidomics studies revealed a dynamic alteration of the membrane lipid composition in human cancer tissues, 21 and distinct lipid profiles correlated with tumor grade. 22 Moreover, combination of molecular biology and lipidomics techniques revealed some of the mechanisms underlying deregulated lipid metabolism in cancer.…”
Section: Introductionmentioning
confidence: 99%